(untitled) (Journal of the College of Basic Education, 2024)
Between 1982-2003, education in the Emirate of Ras Al Khaimah witnessed comprehensive development in its various sectors, keeping pace with scientific and technological development and suiting the social and economic needs of the Emirate and the Union State, thanks to the financial abundance it enjoyed through oil imports. This resulted in outputs represented by a rise Number of schools, students studying in them, and educational staff . The emirate also witnessed a comprehensive campaign to eradicate illiteracy and adult education, and statistical data indicated a qualitative leap in the decline in the number of illiterates. The educational policy followed between 1982-2003 sought to spread education throughout the emirate, and provide it to all age groups, both citizens and residents. With the increase in educational development, education has become an effective force in developing the social and economic fields to achieve the emirate’s renaissance and progress.